2017
DOI: 10.2485/jhtb.26.223
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Potential of Demineralized Dentin Matrix as Bone Graft Material

Abstract: The aim of this study was to evaluate the osteogenic potential of demineralized dentin matrix (DDM) in supporting the osteogenic activity of MG-63 cells and compare it to a mixture of inorganic bovine bone and collagen (Bio-Oss Collagen ® ). Cell morphology, differentiation, adhesion, and growth were investigated via scanning electron microscopy and immunofluorescence analyses of F-actin, osteocalcin, and osteonectin. Cell adhesion and growth on the DDM as a bone graft material were more abundant, with cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Hyo et al evaluated the osteogenetic potential activity of a DDM (dentin demineralized matrix) in supporting the osteogenetic activity of MG-63 cells and compared it to a mixture of inorganic materials. Immunofluorescence assays showed that the fluorescence intensities of osteocalcin and osteonectin as biomarkers of cellular differentiation were higher on the DDM than a comparative specimen [18]. Non-significant differences in osteogenic activity between contaminated ADDM and the group after sterilization using EO gas were confirmed [19].…”
Section: Introductionmentioning
confidence: 82%
“…Hyo et al evaluated the osteogenetic potential activity of a DDM (dentin demineralized matrix) in supporting the osteogenetic activity of MG-63 cells and compared it to a mixture of inorganic materials. Immunofluorescence assays showed that the fluorescence intensities of osteocalcin and osteonectin as biomarkers of cellular differentiation were higher on the DDM than a comparative specimen [18]. Non-significant differences in osteogenic activity between contaminated ADDM and the group after sterilization using EO gas were confirmed [19].…”
Section: Introductionmentioning
confidence: 82%
“…The surface analysis using SEM showed TDBS after the chemical treatment had less occlusion of the dentinal tubules leading to diffusion of more growth factors and exposure of collagen matrix 10,19,36) that might increase bone formation and resorption. This study also showed the resemblance of TDBS to Bio-Oss ® and OraGRAFT ® in terms of the density, roughness, and homogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…We developed two types of DDM (AutoBT®): one is powder, the other is block. The clinical efficacy and safety of DDM powder and block have been approved as new health technology assessment (nHTA) in Korea 2015 based on the several experimental and clinical evidences [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%